Focused Cardiac Ultrasound in Pediatric Pulmonary Hypertension. Issue 4 (April 2019) - Noorbakhsh, Kathleen A.; Bell-Cheddar, Yolandee R.; Marin, Jennifer R.
Abstract : Abstract: We present 2 cases of pediatric pulmonary hypertension presenting with respiratory distress. Focused cardiac ultrasound revealed findings consistent with right ventricular dilatation and elevated right ventricular pressure. These findings, in conjunction with the clinical presentation, allowed for early identification and rapid evaluation of a pathologic process that can often go unidentified. In this report, we review the relevant aspects of focused cardiac ultrasound in the setting of pulmonary hypertension. Abstract : Supplemental digital content is available in the text.